Assessing Instructional Leadership Practices of School Principals in the UAE’s Public Schools and Their Impacts on Teaching and Learning - Alawadhi, Azzah Abdulkarim Abdool (2024)
Within educational settings, instructional leadership is essential in determining how well students are taught and how much they learn. This research examines instructional leadership techniques of school leaders and the influence of these practices on learning and teaching within the framework of the public-school system in the United Arab Emirates. Document analysis and literature review approaches are used through a review of pertinent research literature and policy documents that examine current theories, guidelines and empirical research on instructional leadership in UAE public schools. The finding of this paper provides insights into effective leadership strategies, modifications to the quality of instruction, improved student outcomes and recommendations for policy and training programs targeted at optimizing educational leadership and performance in UAE public schools. It offers suggestions to increase instructional quality and enhance teaching and learning results in UAE public schools. The implication of the finding is that it highlights the impact of effective instructional leadership as used by educational leaders and practitioners in the UAE on teaching quality, student learning results, and overall school improvement within the distinct cultural, social, and educational features of the UAE. The study encourages policymakers to promote initiatives that influence the overall practice of instructional leadership.